Implementasi manajemen strategi untuk meningkatkan kinerja keuangan bank syariah - Setyawan, Ahmad Bayu (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the implementation of strategic management in improving the financial performance of Islamic banks in Indonesia. The background of this study is based on the increasing competition in the banking industry as well as the demands for applying Sharia principles in every aspect of management. The research method uses a descriptive qualitative approach by reviewing literature from various journals and official reports of Islamic financial institutions. Data were obtained through a literature study of five main scientific sources discussing management strategies, product innovation, and their impact on the financial performance of Islamic banks. The results of the study indicate that the implementation of strategic management, which includes planning, implementation, and evaluation, has a positive effect on the profitability, efficiency, and financial stability of Islamic banks. In conclusion, the success of Islamic banks in improving financial performance heavily depends on the management's ability to formulate appropriate strategies. with Sharia principles, innovative, and adaptive to changes in the business environment.